The Proposal for a Single Title System Under the National Land Code 1965: Between Theory and Reality - Sufian, Azlinor; Mohamad, Nor Asiah (Kanun: Jurnal Undang-undang Malaysia; Vol 27 No 2 (2015): KANUN: Jurnal Undang-undang Malaysia Volume 27 Number 2 July 2015, 2015)
Malaysia is moving towards improving its land administration delivery system by implementing electronic conveyancing. This is evident through the submission of a proposal paper forwarded by the Department of the Director-General of Land and Mines, Ministry of Natural Resources and Environment. One of the proposals is concerning the implementation of a single-title system as a path to assist the implementation of an electronic land administration system. The proposal was made based on the view that the existing system of having two titles at Registry Title Office and District Land Office level has created numerous land legister databases at state level. This paper was prepared employing a qualitative research methodology. The paper is aimed to analyse the viability of the implementation of a single title and its relation to the computerised land registration system and e-alienation. Keywords: land title, land office title, state authority, registration